Trajectories of care for children and adolescents with psychosocial problems: a 3‐year prospective cohort study. (20th October 2019) - Verhage, Vera; Jansen, Danielle E.M.C.; Almansa, Josue; Wunderink, Charlotte; Grietens, Hans; Reijneveld, Sijmen A.
Abstract : Background: Care for children and adolescents with psychosocial problems is aimed at reducing problems. There may be a relationship between the intensity and duration of care provision and improvement of these outcomes, but evidence on this issue is lacking. We therefore examined the association between care trajectories based on duration and intensity of care for children, and the reduction in psychosocial problems after 3 years. Methods: We obtained a cohort of all children entering psychosocial care in one region ( n  = 1, 378), the TAKECARE cohort, and followed it for 3 years, with five assessment rounds. Retention in the final round was 85.8%. Psychosocial problems were measured using the parent report of the Total Difficulty Score of the Strength and Difficulties Questionnaire (SDQ‐TDS). We constructed trajectories for intensity of care using growth mixture modelling and assessed the association between duration and intensity of care trajectories and SDQ‐TDS after 3 years. Results: After 3 months 60.6% of children and adolescents were receiving care, after 1 year 38.7% were receiving care and after 3 years 26.0%. Regarding intensity of care, three trajectories were found: one with minimal intensity during all 3 years, a second with initially medium intensity and strong reduction within 1 year, and a third with high intensity and a reduction after 1 year. Although the psychosocial problems of children and adolescents were reduced during the 3‐year period, the rate of decline was relatively less marked for children and adolescents with longer care trajectories. Conclusion: Overall, children and adolescents with psychosocial problems who received care had improved outcomes at follow‐up. However, increased provision of care does not automatically lead to reduction of problems, and although overall psychosocial problems are reduced, a substantial subgroup has longer lasting problems.